2010
DOI: 10.3109/13625187.2010.535871
|View full text |Cite
|
Sign up to set email alerts
|

Women's views and experiences of their vaginal bleeding patterns: An international perspective from Norplant users

Abstract: Despite growing acceptance of altering bleeding patterns, women in this study preferred monthly vaginal bleeding. Understanding sociocultural contexts and individual preferences is important when addressing this issue with women from diverse backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In contrast, no significant differences in preference for amenorrhea by age group were found in studies in Nigeria, South Africa, Scotland, Italy [55,67]. Younger women were also generally more likely to desire less frequent (but non-amenorrheic) menstrual bleeding patterns [56,60,66,68,70]. A Swiss study found that while 37% of women preferred monthly bleeding, nearly as many (32%) preferred an interval of 2-6 months, with women aged 15-19 most likely to prefer two-monthly intervals [53].…”
Section: Women's Responses Related To Contraceptive-induced Amenorrhea and Other Non-standard Bleeding Frequenciesmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, no significant differences in preference for amenorrhea by age group were found in studies in Nigeria, South Africa, Scotland, Italy [55,67]. Younger women were also generally more likely to desire less frequent (but non-amenorrheic) menstrual bleeding patterns [56,60,66,68,70]. A Swiss study found that while 37% of women preferred monthly bleeding, nearly as many (32%) preferred an interval of 2-6 months, with women aged 15-19 most likely to prefer two-monthly intervals [53].…”
Section: Women's Responses Related To Contraceptive-induced Amenorrhea and Other Non-standard Bleeding Frequenciesmentioning
confidence: 75%
“…Across included surveys, women's preference for amenorrhea ranged between 0% [56] (in Tunisia) and 65% [57] (in Brazil) (Table 2) [53,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Preferences for regular, non-monthly menstrual cycles (i.e., various durations of longer than one month but less than one year) ranged between 0% [56] (in Indonesia) and 66% [68] (in Mexico). Generally, amenorrhea appears more commonly preferred in North America, Europe and South America, whereas trends for other bleeding pattern preferences are less prominent (Table 2).…”
Section: Women's Responses Related To Contraceptive-induced Amenorrhea and Other Non-standard Bleeding Frequenciesmentioning
confidence: 99%
“…In many cultures, sexual activity during menstruation is not accepted and contraceptive users may fear prolonged bleeding will cause friction in their relationships and that their partners will seek extramarital relationships. 55 , 56 In some cultures, people are expected to socially isolate during menstruation, which further limits their daily activities and may even expose them to harms. 57 In addition, the management of the bleeding itself can be a challenge, especially when menstrual products are inaccessible, unaffordable, and/or low-quality.…”
Section: Biological Linkages Between Mh and Srhrmentioning
confidence: 99%
“…It also provided women with a method to regulate their monthly bleeding, mimicking a regular menstrual cycle 1. More recent developments in hormonal contraception have given women additional options for control over their monthly bleed 2. Women can manipulate their combined oral contraceptive regime in order to decrease bleeding episodes,3 4 or use progestogen-only methods of contraception that may eliminate bleeding altogether.…”
Section: Introductionmentioning
confidence: 99%